Determinan Ekspor Batu Bara Indonesia Serta Kontribusinya Terhadap Ekspor Pertambangan dan Pendapatan Negara - Rosita, Ratih; Asrini, Asrini; Veronica, Deka (Haka Vyza Media, 2023)
Study This title “ Determinants of Indonesian Coal Exports and Their Contribution To Export Mining and State Revenue ”. As for objective from study This that is For know development as well as influence price , exchange rate And production rock coals to export stone in Indonesia. Objective next that is analyze contribution sector mining to state income. Method research used _ is analysis quantitative with secondary data in the form of export data new ember , export data mining And income country period 2013-2021 sourced _ from BPS. For analyze influence price , exchange rate to production rock coals use multiple linear regression , whereas For analyze contribution mining export rock coal in Indonesia uses equality Contribution. Results analysis concludes , first export rock coals as well as his contribution to export mining And income country during 2013-2021 period with fluctuating conditions , respectively _ Partial Exchange rate And Production influential significant to coal exports in Indonesia meanwhile in a manner contribution obtained mark more big than 50%, that is sector mining contribute very Good to GDP in Indonesia during period 2013-2021.